2016
DOI: 10.1186/s13054-016-1558-0
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound can be used to predict the potential of prone positioning and assess prognosis in patients with acute respiratory distress syndrome

Abstract: BackgroundIt is very important to assess the effectiveness of prone positioning (PP) in patients with severe acute respiratory distress syndrome (ARDS). However, it is difficult to identify patients who may benefit from PP. The purpose of this study was to investigate whether prone positioning potential (PPP) can be predicted by lung ultrasound in patients with ARDS.MethodsIn this prospective study, 45 patients with ARDS were included for the assessment of PPP. A PP lung ultrasound examination (PLUE) protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 19 publications
2
74
0
3
Order By: Relevance
“…In 45 patients with moderate to severe ARDS, Wang et al found that a reduction of 5.5 points or higher in the lung US score for dependent lung regions in the prone position (3 hours after prone positioning) correlated with a Pa o 2 /Fi o 2 ratio of greater than 300 after 7 days (prone positioning potential–positive group), and those with a lung US score reduction of 7 or higher correlated with improved survival. The authors did not find a correlation between the lung US score variation and oxygenation at 3 hours after prone positioning, but they did find a significant improvement in the dead space .…”
Section: Literature Regarding Lung Us For Monitoring Aeration In Ardsmentioning
confidence: 99%
“…In 45 patients with moderate to severe ARDS, Wang et al found that a reduction of 5.5 points or higher in the lung US score for dependent lung regions in the prone position (3 hours after prone positioning) correlated with a Pa o 2 /Fi o 2 ratio of greater than 300 after 7 days (prone positioning potential–positive group), and those with a lung US score reduction of 7 or higher correlated with improved survival. The authors did not find a correlation between the lung US score variation and oxygenation at 3 hours after prone positioning, but they did find a significant improvement in the dead space .…”
Section: Literature Regarding Lung Us For Monitoring Aeration In Ardsmentioning
confidence: 99%
“…In conclusion, while providing unessential or dangerous statements, this Commentary seems to overlook the strong evidence behind the use of semiquantitative LUS in critically ill patients of any age. In fact, several US scores, carrying all of the intrinsic characteristics due to their semiquantitative nature and being even simpler than the neonatal one, have been validated against a multitude of techniques (Table ), confirming their usefulness despite their intrinsic limitations . Table is not comprehensive, but it is out of the scope of this article to list all LUS validation studies.…”
Section: Examples Of Studies Validating Lus Scores Against Various Mementioning
confidence: 97%
“…In this regard, chest computed tomography cannot be routinely used in daily clinical practice to monitor aeration improvement, while lung ultrasonography represents a valid bedside alternative for this purpose. 5 Indeed, ultrasound could be a viable option to reduce the need to transport patients to the radiology department, reducing the exposure of hospital staff and other subjects to COVID-19 patients. Pan et al have recently highlighted that lung recruitability can be effectively assessed bedside in COVID-19 patients with ARDS.…”
Section: Intubation and Ventilation Amid Covid-19: Commentmentioning
confidence: 99%
“…2 Similar results were presented by Wang et al, who reported that bedside lung ultrasonography can be adopted to guide response to prone positioning. 5 It is important to remember that the use of positive pressure cycles remains associated with potential adverse effects such as an increased risk of unintended extubation and/or secondary hemodynamic effects, and the real impact of this strategy in COVID-19 patients with previous cardiac disease remains unknown. For these reasons, the use of lung ultrasound could further implement the use of a personalized approach to the ARDS management and related ventilatory support.…”
Section: Intubation and Ventilation Amid Covid-19: Commentmentioning
confidence: 99%
See 1 more Smart Citation